Improving eleventh graders’ oral production in english class through cooperative learning strategies (2007)
This paper aims to report on research carried out with eleventh graders at Colegio de Bachillerato Patria in Bogotá. The main objective of the research was to establish strategies to help students to improve their oral production in English. Instruments used to collect the data were: field notes, students’ and teachers’ surveys, students’ interviews and audiotapes recordings. Considering the data gathered, this research prompted a more cooperative environment among students in the oral process. Finally it was a way to motivate other teachers in the school to work with these kinds of strategies. Key words: Cooperative learning strategies, oral interaction, interaction activities, collaborative learning El propósito de este artículo es presentar una investigación que se llevó a cabo con estudiantes de grado undécimo del Colegio de bachillerato Patria en Bogotá. El principal objetivo consistió en establecer estrategias que ayudaran a los estudiantes a mejorar su producción oral en inglés. Los instrumentos utilizados para recolectar información fueron diarios de campo, encuestas a estudiantes y profesores, entrevistas a estudiantes, grabaciones de audio y video. Considerando la información recolectada, este estudio promovió un ambiente de más cooperación entre los estudiantes. Finalmente fue una manera de motivar a otros docentes en el colegio a trabajar con este tipo de estrategias. Palabras Clave: Estrategias del aprendizaje cooperativo, interacción oral, actividades de interacción, aprendizaje colaborativo